Thinking Intimate Geopolitics Creatively: Choreographing Spaces of Performance, Testimony, and Law. Issue 1 (2nd January 2020) - Veal, Charlotte
Abstract : Testimony has featured as a defining framework for post-Apartheid South Africa in traditional courts of law and under the guise of Truth and Reconciliation. Yet South Africa's effort to transition to postviolence must be read as partial, with rates of gender-based violence amongst some of the highest in the world. The article traces the convergence between performance and testimony. It examines creative efforts to respond to South Africa's cult of masculinity, which positions women as "fair game, " and judicial ambivalence to perpetrators of violence. I turn to the testimonial-come-documentary dance Slavery to examine the critical and creative possibilities of dance performance to testify to the absent presence of this national crisis, rhetorically probe dancers, and audiences alike to find opportunities for its contestation, whilst questioning how and even if the arts are best placed to respond to judicial failings. The article introduces three distinct dance spatialities—esthetic, ethical and political space—through which offstage enactments of gender-based violence are upstaged and contested. Nonetheless, these are presented as deeply contentious spaces, in which new silences and violences of the body can be enabled, and where performance risks operating as a "third assailant." The article calls for greater critical conceptual attention to thinking intimate geopolitics through creative performance.